Efecto de la dramatización para la inferencia de textos en los estudiantes de tercer grado de la institución educativa dolores maría ucrós sede eufemia benedetti en soledad - atlántico (2019)
In order to improve the deficiencies in the inferential reading level, found in the third grade students of the Dolores Maria Ucrós Educational Institution in Soledad - Atlántico, it is stated “The effect of dramatization as a strategy to strengthen this reading level; Through this pedagogical strategy, students are expected to move to the second level of reading comprehension and be able to infer texts in different contexts. It will be conceived under the parameters of the quantitative approach and dimensioned from an epistemological, empirical analytical paradigm and the design will be quasi-experimental. This research is pertinent because by improving the inferential level in reading comprehension, students will reach the critical level of reading and will be able to relate the texts to their previous knowledge, improve academic processes and results in internal and external tests.